Understanding of and attitudes to genetic testing for inherited retinal disease: a patient perspective. Issue 9 (28th June 2013) - Willis, T A; Potrata, B; Ahmed, M; Hewison, J; Gale, R; Downey, L; McKibbin, M
Abstract : Background/aims: The views of people with inherited retinal disease are important to help develop health policy and plan services. This study aimed to record levels of understanding of and attitudes to genetic testing for inherited retinal disease, and views on the availability of testing. Methods: Telephone questionnaires comprising quantitative and qualitative items were completed with adults with inherited retinal disease. Participants were recruited via postal invitation (response rate 48%), approach at clinic or newsletters of relevant charitable organisations. Results: Questionnaires were completed with 200 participants. Responses indicated that participants' perceived understanding of genetic testing for inherited retinal disease was variable. The majority (90%) considered testing to be good/very good and would be likely to undergo genetic testing (90%) if offered. Most supported the provision of diagnostic (97%) and predictive (92%) testing, but support was less strong for testing as part of reproductive planning. Most (87%) agreed with the statement that testing should be offered only after the individual has received genetic counselling from a professional. Subgroup analyses revealed differences associated with participant age, gender, education level and ethnicity (p<0.02). Participants reported a range of perceived benefits (eg, family planning, access to treatment) and risks (eg, impact upon family relationships, emotional consequences). Conclusions: Adults with inherited retinal disease strongly support the provision of publicly funded genetic testing. Support was stronger for diagnostic and predictive testing than for testing as part of reproductive planning.